Interactions Between Suspended Kaolinite Deposition and Hyporheic Exchange Flux Under Losing and Gaining Flow Conditions. Issue 9 (15th May 2018) - Fox, Aryeh; Packman, Aaron I.; Boano, Fulvio; Phillips, Colin B.; Arnon, Shai
Abstract: Fine particle deposition and streambed clogging affect many ecological and biogeochemical processes, but little is known about the effects of groundwater flow into and out of rivers on clogging. We evaluated the effects of losing and gaining flow on the deposition of suspended kaolinite clay particles in a sand streambed and the resulting changes in rates and patterns of hyporheic exchange flux (HEF). Observations of clay deposition from the water column, clay accumulation in the streambed sediments, and water exchange with the bed demonstrated that clay deposition in the bed substantially reduced both HEF and the size of the hyporheic zone. Clay deposition and HEF were strongly coupled, leading to rapid clogging in areas of water and clay influx into the bed. Local clogging diverted exchanged water laterally, producing clay deposit layers that reduced vertical hyporheic flow and favored horizontal flow. Under gaining conditions, HEF was spatially constrained by upwelling water, which focused clay deposition in a small region on the upstream side of each bed form. Because the area of inflow into the bed was smallest under gaining conditions, local clogging required less clay mass under gaining conditions than neutral or losing conditions. These results indicate that losing and gaining flow conditions need to be considered in assessments of hyporheic exchange, fine particle dynamics in streams, and streambed clogging and restoration. Plain Language Summary: Deposition and accumulation of excessive amounts of clay and silt is one of the common causes of degradation of river ecosystems. We conducted experiments to evaluate the effects of flow from the stream into the groundwater (losing stream) and from the groundwater into the stream (gaining stream) on the deposition of clay particles in a sand bed and the resulting changes in water exchange between the stream and the subsurface. We found that clay deposition substantially reduced water exchange due to clogging. Computer simulations of this process revealed that the locations of clogging are closely related to locations where water exchange occurred, but these patterns differed in losing and gaining streams. This type of clay accumulation influences water budgets in streams and reduces connectivity between streams, floodplains, and the underlying aquifers. Such a reduction in connectivity may negatively affect water resources, ecosystem functions, and river resilience. These results indicate that losing and gaining flow conditions in streams need to be considered in assessments of streambed clogging and river restoration. Key Points: Suspended particle deposition dynamics were different under losing flow conditions as compared to gaining flow conditions Pore clogging processes significantly reduce the hyporheic exchange flux for all tested flow conditions Experiments reveal that fine particle deposition and clogging causes increased subsurface lateral flow